Drawing the Line: A Legal Geography of Street Art in the London Borough of Tower Hamlets - Ward, Tom (Street Art & Urban Creativity, 2022)
This article presents the findings of a small study that examines how and why the London Borough of Tower Hamlets introduced a policy in 2019 to distinguish between graffiti and street art. In doing so, this study adopts the theoretical vocabulary of legal geography to intervene in debates concerning the distinction between graffiti and street art. The research begins by outlining East London as a site of empirical interest, before defining several concepts in legal geography that are argued to be of analytical use for graffiti and street art scholars. The methodology of the study is presented before describing the results: that street art is selectively retained in Tower Hamlets because it valorises and decorates property where graffiti is considered to threaten the dominance of property in the spatial imagination of the law. As such, legal geography is presented as a critical tool to interrogate the instrumentalisation of policies, like that in Tower Hamlets, that seek to regulate what can be termed street art.